The Influence of Audio Visual Media On Students' Listening Skills In Indonesian Language Subjects For Grade III Elementary School Negeri 1 Segeran Indramayu - Farihiyah (International Journal of Science and Environment (IJSE), 2026)
This study aims to determine the effect of audio-visual media on the listening skills of third-grade students of SD Negeri 1 Segeran Indramayu. The background of the study shows that students' listening skills are still low due to conventional learning, where teachers only read stories without the support of interesting media. The study involved 20 students with a pre-test and post-test design. The research method used in this study is experimental research. The pre-test results showed scores in the range of 30%–80% with an average of 53.5%, where 65% of students were included in the sufficient and low categories. After the use of audio-visual media, the post-test scores increased significantly with a range of 70%–100% and an average of 89.0%, and all students (100%) reached the skilled category. The distribution of post-test scores shows that 40% of students are in the 90–99 interval and 20% reach a score of 100. The results of statistical tests show that the pre-test data is normally distributed (sig = 0.131 > 0.05), while the post-test is not normal (sig = 0.010 < 0.05), but the homogeneity test shows homogeneous variance (sig = 0.814 > 0.05). The Paired Sample T-Test test produces a significance value of 0.000 < 0.05, so there is a significant difference between the pre-test and post-test. Thus, audio-visual media is proven to have a significant and effective effect in improving students' listening skills.